"Presentism" Versus "Path Dependence"?: Reflections on the Second World War in Russian Textbooks of the 1990s. Issue 1 (1st March 2021) - Ehrlich, Serguey
Abstract: In the fifteen Russian textbooks of the 1990s examined in this article, the Second World War is subject to three levels of reflection: language, narrative templates, and the representation of contested events. The language used in the textbooks represents an amalgam of Soviet propagandistic clichés and uncritically adopted Western terminology. These textbooks also retain the same "schematic narrative template" of the Second World War, based on references to the expulsion of foreign enemies, found in Soviet textbooks. Significant transformations can be observed only in the representation of events, in which the authors' harsh criticism of Stalin's crimes comes to the fore. Yet these superficial changes did not alter the basic structures of history learning, which was one of the main reasons why working through the past during the Yeltsin era almost failed.